Homicídios e desigualdades sociais no Município de São Paulo Social inequality and homicide rates in Sao Paulo City, Brazil - Vilma Pinheiro Gawryszewski; Luciana Scarlazzari Costa (Revista de Saúde Pública, 2005)
OBJETIVO: A relação entre renda e mortalidade por violência vem sendo estudada nos últimos anos. A Síntese de Indicadores Sociais 2002, lançada pelo IBGE, refere que o traço mais marcante da sociedade brasileira é a desigualdade. O propósito do estudo é testar a associação entre as taxas de homicídios e alguns indicadores de saúde e socioeconômicos. MÉTODOS: Estudo ecológico, de corte transversal. Foram analisados dados do Município de São Paulo, ano 2000, quanto a coeficientes de homicídios e cinco indicadores: taxa de mortalidade infantil, renda média do chefe de família, percentual de adolescentes de 15 a 17 anos que não freqüentavam a escola, percentual de adolescentes grávidas de 14 a 17 anos e densidade demográfica. Para testar essas associações foram utilizados o coeficiente de correlação de Pearson e a regressão linear múltipla. RESULTADOS: O coeficiente de homicídios foi 57,3/100.000. A correlação entre taxas de homicídios e renda média foi negativa e forte (r=-0,65). Maiores coeficientes foram encontrados nos distritos com menor renda e menores naqueles com maiores rendas. Para o percentual de adolescentes que não freqüentavam a escola (r=0,68) e para o percentual de adolescentes grávidas (r=0,67) a associação encontrada foi positiva e forte. Para a taxa de mortalidade infantil a correlação encontrada foi r=0,24 (para todos p<0,05). A densidade demográfica não apresentou correlação significativa com o coeficiente de homicídios. Na análise de regressão linear múltipla foram significativas somente as variáveis renda média (negativa), trabalhada com o seu logaritmo e percentual de adolescentes que não freqüentavam a escola (positiva) (para ambos indicadores: p<0,01). CONCLUSÕES: Os achados apontam para o problema dos homicídios e sua relação com as disparidades socioeconômicas do Município de São Paulo. O desenvolvimento econômico e a redução das iniqüidades podem ter impacto nas taxas de mortalidade violenta. OBJECTIVE: The relation between income and mortality due to violence has been studied in recent years. The Synthesis of Social Indicators of 2002 [Síntese de Indicadores Sociais, 2002], published by The Brazilian Institute of Geography and Statistics (IBGE), states that one of the most outstanding characteristic of Brazilian society is inequality. The proposal of this ecological study was to test the association between homicide rates, and some health and socioeconomic indicators. METHODS: This is an ecological cross-sectional study. Data regarding Sao Paulo City, Brazil in the year 2000 was analyzed. The association between homicide coefficients and the following five indicators were tested: infant mortality rates, monthly average income of household heads, percentage of adolescents aged 15 to 17 years not attending school, proportion of pregnant adolescent women aged 14 to 17 years and demographic density. Pearson's correlation coefficient and a multiple linear regression model were utilized to test these associations. RESULTS: The municipal homicide rate was 57.3/100,000. The correlation between homicide rates and average monthly income was strong and negative (r=-0.65). Higher homicide rates were found in the districts whose inhabitants had lower incomes and lower rates were found in those districts whose inhabitants had higher incomes. The correlation between homicide rates and proportion of adolescents not attending school was positive and strong (r=0.68). The correlation between homicide rates and the proportion of pregnant adolescent women was positive and strong (r=0.67). The correlation between homicides and the rate of infant mortality was r=0.24 (for all: p<0.05). The correlation between demographic density and homicides was not significant. Although the univariate regression was positive for four indicators, the multivariate regression test was only significant for average monthly income (negative) and proportion of adolescents not attending school (positive) (for both indicators: p<0.01). CONCLUSIONS: The findings highlight the problem of homicides and socioeconomic disparities in S. Paulo City. Economic development and reducing socioeconomic inequality may have an impact on the rates of mortality due to violence.